(untitled) (Journal of history, 2026)
The article presents the studied information about prisoners of war who were captured as a result of the Great Patriotic War of 1941-1945 in South Kazakhstan and subsequently captured in the same regions, their contribution and role in the socio-economic development of the region. If you look at the general history, you can see a huge number of pages. One of them is the situations that occurred during the Great Patriotic War and the problems that took place after the war. These historical events were not openly spoken and written about anywhere before Kazakhstan gained independence. That is, all archives were stored on the pages in a "top secret" form and were in a closed state. Nevertheless, not every historian could openly conduct his research on this topic, delving into archival materials. The ban from above and the lack of access to archival materials were even more relevant in that the study of these topics was prohibited. This article also criticizes the consequences of the leftist policies pursued by Stalin, the leader and main ruler of the Soviet government, which was a huge giant empire during the war. Along with the prisoners of war, the migrations of massive peoples, who suffered equally in those dark times, were also accompanied.